Balloon-Assisted Tracking: A Solution to Severe Subclavian Tortuosity Encountered During Transradial Primary PCI - Dharma, Surya; Gilchrist, Ian C.; Patel, Tejas (International Journal of Angiology, 2016)
Radial artery access is preferred over femoral access for primary percutaneous coronary intervention (PCI) in patients with acute ST-segment elevation myocardial infarction because of the reduction in access site complications and mortality associated with the radial artery access. Successful transradial primary PCI requires knowledge of techniques to handle unexpected severe subclavian artery tortuosity. Balloon-assisted tracking (BAT) is one technique developed to negotiate the tortuosity and loops in the upper extremity. However, the use of BAT in dealing with a severe subclavian loop during a transradial primary PCI procedure has never been reported. We described a case of transradial primary PCI with severe subclavian artery loop that was negotiated successfully by the BAT technique.
Keywords: radial artery access; balloon-assisted tracking; subclavian artery loop; primary PCI